Cost-effectiveness of annual versus biennial screening mammography for women with high mammographic breast density. (December 2014) - Pataky, Reka; Ismail, Zahra; Coldman, Andrew J; Elwood, Mark; Gelmon, Karen; Hedden, Lindsay; Hislop, Greg; Kan, Lisa; McCoy, Bonnie; Olivotto, Ivo A; Peacock, Stuart
Objectives: The sensitivity of screening mammography is much lower among women who have dense breast tissue, compared with women who have largely fatty breasts, and they are also at much higher risk of developing the disease. Increasing mammography screening frequency from biennially to annually has been suggested as a policy option to address the elevated risk in this population. The purpose of this study was to assess the cost-effectiveness of annual versus biennial screening mammography among women aged 50–79 with dense breast tissue. Methods: A Markov model was constructed based on screening, diagnostic, and treatment pathways for the population-based screening and cancer care programme in British Columbia, Canada. Model probabilities and screening costs were calculated from screening programme data. Costs for breast cancer treatment were calculated from treatment data, and utility values were obtained from the literature. Incremental cost-effectiveness was expressed as cost per quality adjusted life year (QALY), and probabilistic sensitivity analysis was conducted. Results: Compared with biennial screening, annual screening generated an additional 0.0014 QALYs (95% CI: −0.0480–0.0359) at a cost of $819 ($ = Canadian dollars) per patient (95% CI: 506–1185), resulting in an incremental cost effectiveness ratio of $565, 912/QALY. Annual screening had a 37.5% probability of being cost-effective at a willingness-to-pay threshold of $100, 000/QALY. Conclusion: There is considerable uncertainty about the incremental cost-effectiveness of annual mammography. Further research on the comparative effectiveness of screening strategies for women with high mammographic breast density is warranted, particularly as digital mammography and density measurement become more widespread, before cost-effectiveness can be reevaluated.